Sistem Informasi Geografis Untuk Prediksi Perkembangan Fisik Kota (Studi Kasus Kota Singaraja-Bali) - Putra, I Wayan Krisna Eka; Sriartha, I Putu (Jurnal Nasional Pendidikan Teknik Informatika (JANAPATI), 2013)
This study is one of the design of Geographic Information Systems (GIS) for modeling simulations to predictive of the physical development in Singaraja City, so as to provide fast data regarding the Â estimation of the physical development of cities among rapid land conversion activities. The method used in this study was done on a number of spatial data overlay thought to affect the physical development of the city. Each of the spatial data is weighted according to the likelihood that the effect will be given. Results from this study defines that land has been earmarked for housing and public facilities and infrastructure in Singaraja around about 39%. While the predictions of the results found that the location of the most potential physical development of the city will occur at the core of the city and partly penetrated the membrane core of the city as well as suburban.